FIQH MUAMALAH DALAM ERA CRYPTOCURRENCY: TINJAUAN HUKUM ISLAM KONTEMPORER - Rahmawati; Muhammad Yazid (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the perspective of fiqh muamalah and contemporary Islamic law on the use of cryptocurrency in the modern economic system. The rapid advancement of digital technology has led to the emergence of cryptocurrencies such as Bitcoin, Ethereum, and other digital assets that function as means of payment and investment instruments. The main advantage of cryptocurrency lies in its decentralized system and the use of blockchain technology, which ensures security and transparency of transactions without the involvement of third parties. However, from an Islamic perspective, the use of cryptocurrency remains controversial due to the presence of gharar (uncertainty), maysir (speculation), and dharar (harm), arising from high price volatility, the absence of real asset backing, and its potential misuse for illegal activities. This research employs a qualitative descriptive method through a literature review of various scholarly sources, fatwas issued by the Indonesian Ulema Council (MUI), and opinions of contemporary Islamic scholars. The results indicate that most scholars view cryptocurrency as not meeting the criteria of a legitimate medium of exchange in Islam because it lacks intrinsic value and official recognition by state authorities. Nonetheless, Islam does not reject technological innovation as long as it aligns with sharia principles. Therefore, cryptocurrency may be acceptable if it is properly regulated, backed by tangible assets, and adheres to the principles of justice, transparency, and security in accordance with the objectives of maqāṣid al-sharī‘ah to preserve public welfare.